2015
DOI: 10.1091/mbc.e14-09-1342
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the cellular mechanism of the yeast ubiquitin ligase APC/C-Cdh1 from the analysis of in vivo degrons

Abstract: In vivo analysis in budding yeast identifies APC/C-Cdh1–specific minimal degrons carrying either a D or a KEN box and a nuclear localization sequence. APC/C-Cdh1 activity is restricted to the nucleus, maximal in the nucleoplasm, and absent from the cytoplasm, allowing for spatiotemporal control of Cdh1 substrate proteolysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 66 publications
0
25
0
Order By: Relevance
“…However, our results clearly demonstrate that Spo12 degradation by the APC/C is dependent on functional D-and KEN-box receptor sites, suggesting either that mutation of Spo12 degrons renders the protein unstable independent of the APC/C or that cryptic D-and KEN-boxes exist. Additional structural studies will be crucial in the future to characterize how consensus and non-consensus degron sequences can bind the same receptor sites to promote substrate ubiquitylation, and it still remains unclear which docking sites some of the alternative degrons reported for APC/C substrates bind to and which may contribute to degradation in other ways aside from binding the co-activator, for example by promoting nuclear localization (34). Given the prevalence of unconventional degron motifs in Cdh1 substrates from other species and the high conservation of APC/C core and co-activator subunits, our findings likely have general relevance to APC/C substrate recognition in all eukaryotes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our results clearly demonstrate that Spo12 degradation by the APC/C is dependent on functional D-and KEN-box receptor sites, suggesting either that mutation of Spo12 degrons renders the protein unstable independent of the APC/C or that cryptic D-and KEN-boxes exist. Additional structural studies will be crucial in the future to characterize how consensus and non-consensus degron sequences can bind the same receptor sites to promote substrate ubiquitylation, and it still remains unclear which docking sites some of the alternative degrons reported for APC/C substrates bind to and which may contribute to degradation in other ways aside from binding the co-activator, for example by promoting nuclear localization (34). Given the prevalence of unconventional degron motifs in Cdh1 substrates from other species and the high conservation of APC/C core and co-activator subunits, our findings likely have general relevance to APC/C substrate recognition in all eukaryotes.…”
Section: Discussionmentioning
confidence: 99%
“…budding yeast Iqg1 (30), Cik1 (31), and Kip1 (32) and human Usp1 (33)) for which extended regions have been identified as sufficient and/or necessary for degradation but that lack consensus D-and KEN-box motifs. Nuclear localization also appears to be required for degradation of APC/C substrates in budding yeast (34), and therefore some degrons may act by promoting nuclear import and not by binding the APC/C or its co-activators.…”
mentioning
confidence: 99%
“…The local concentration of active APC/C, and co-localization with its substrates, might regulate target selectivity (Arnold et al, 2015). Several studies have suggested that APC/C Cdh1 activity is spatially restricted (Jaquenoud et al, 2002; Acquaviva et al, 2004; Arnold et al, 2015), and numerous APC/C substrates require nuclear localization for efficient degradation (Hu et al, 2011; Arnold et al, 2015).…”
Section: Substrate Ordering By the Apc/cmentioning
confidence: 99%
“…Several studies have suggested that APC/C Cdh1 activity is spatially restricted (Jaquenoud et al, 2002; Acquaviva et al, 2004; Arnold et al, 2015), and numerous APC/C substrates require nuclear localization for efficient degradation (Hu et al, 2011; Arnold et al, 2015). Export of Cdh1 from the nucleus might contribute to APC/C inactivation, and Cdh1 targets can be stabilized by forcing their cytoplasmic localization (Jaquenoud et al, 2002; Kraft et al, 2003).…”
Section: Substrate Ordering By the Apc/cmentioning
confidence: 99%
“…There are different methods, to monitor rate of protein degradation and estimate protein half‐life, that are currently in hire, including pulse‐chase assay as well as proteome scale methods that rely on mass spectrometry (Lévy et al ; Belle et al ; Cambridge et al ; Bojkowska et al ; Eden et al ; Butko et al ; Kim et al ; Holm et al ; Terweij et al ; Piatkov et al ; Christiano et al ; Cohen et al ; Lu et al ; Arnold et al ; Yu et al ; Fan et al ; Maurer et al ). Notably, two classical biochemical techniques are commonly used to monitor the degradation of intracellular protein fragments and measure a protein's half‐life, particularly pulse‐chase analysis and cycloheximide (CHX) chase assay (Zhou ; Eldeeb and Fahlman ; Oh et al ).…”
Section: Classical Methods For Monitoring Protein Degradationmentioning
confidence: 99%